The educational prospects of traditional games as learning activities of modern students - Vasileva-Stojanovska, Tatjana; Vasileva, Marina; Malinovski, Toni; Trajkovik, Vladimir (My University, 2014)
“Grandma’s games” is an educational case study that introduced few selected traditional games into the regular education of K9 students, attempting to bring together the benefits of traditional outdoor games that our ancestors used to play and the modern technology that is closer to the present generations. The objectives of this project target the educational outcomes while having a strong consideration of the social and emotional aspects of students regarding motivation, joy, positive upbringing patterns and connection to the traditional values expressed in our folklore. We selected six traditional games and introduced three couples of them into the regular curricula of Math, Art and Nature/Society in few sixth grade classes. Each game was carefully selected aiming to improve certain aspect of the learning process with regard to the individual differences in personality, learning style and ability of each student. The games “Hop-scotch” and “Match Box” selected for Math classes were aiming to improve the student’s logical reasoning, expressive skills were enhanced with the aid of “Lady” and “String” games on Art classes, and social skills were developed during the “Mosque” and “Hide and Seek” games on Nature/Society classes. The instructional design for this case study expressed in the teacher’s manual included lesson plan, objectives to be accomplished, detailed description of the game to be used to accomplish certain objective, description of the roles of the teacher and the students, teacher’s guidance to the learners, the expected feedback from the students, and instructions for performance assessment. The game based learning scenario encouraged active participation of all the students in the games, collaboration, and cooperative work on problem solving tasks given during and after the games, active participation of the students in the evaluation process, development of critical thinking, and praising the friendship during the joyful learning activities. While games were played in classical face to face manner, the use of technology was encouraged during the problem solving sessions, collaborative videoconferencing sessions with the peers from the other schools, and to facilitate communication with the peers from the distant parts of the country with aid of social networks. The effects of the selected games on educational outcomes were investigated using multiple criteria including evaluation of the academic performance and overall estimation of the transferable skills as communication, collaboration and interactivity. Our findings suggest that different games impact the learner’s satisfaction, which in turn has significant impact on educational outcomes. The correlation between individual factors (personality; learning style) and experienced satisfaction with different games during the study reveals the importance of personalized approach in education for optimal learning results.
Keywords: educational games, pedagogy, personality, learning style